'Leaving no one behind': a scoping review on the provision of sexual and reproductive health care to nomadic populations - Moazzam Ali; Joanna Paula Cordero; Faria Khan; Rachel Folz (BMC, 2019)
Abstract Backgrund Marginalized groups, such as nomadic populations across the world, have perhaps the least access to modern reproductive health (RH) services. This scoping review aims to identify barriers to access to RH services faced by nomadic populations from the existing literature and to highlight possible opportunities to address them. Methods Key databases, including PubMed, Popline, Google Scholar, and Google Advanced were searched for relevant articles published between 2002 and 2019. A total 344 articles were identified through database online searches, and 31 were included in the review. Results Nomadic people face complex barriers to healthcare access that can be broadly categorized as external (geographic isolation, socio-cultural dynamics, logistical and political factors) and internal (lifestyle, norms and practices, perceptions) factors. To effectively address the needs of nomadic populations, RH services must be available, accessible and acceptable through tailored and culturally sensitive approaches. A combination of fixed and mobile services has proven effective among mobile populations. Low awareness of modern RH services and their benefits is a major barrier to utilization. Partnership with communities through leveraging existing structures, networks and decision-making patterns can ensure that the programmes are effectively implemented. Conclusion Further research is needed to better understand and address the RH needs of nomadic populations. Though existing evidence is limited, opportunities do exist and should be explored. Raising awareness and sensitization training among health providers about the specific needs of nomads is important. Improved education and access to information about the benefits of modern RH care among nomadic communities is needed. Ensuring community participation through involvement of nomadic women and girls, community leaders, male partners, and trained traditional birth attendants are key facilitators in reaching nomads. However, participatory programmes also need to be recognized and supported by governments and existing health systems.